Inefficient recruitment of kinesin-1 to melanosomes precludes it from facilitating their transport - Robinson, Christopher L.; Evans, Richard D.; Briggs, Deborah A.; Ramalho, Jose S.; Hume, Alistair N. (The Company of Biologists, 2017)
Microtubules and F-actin, and associated motor proteins, are considered to play complementary roles in long- and short-range organelle transport. However, there is growing appreciation that myosin/F-actin networks can drive long-range transport. In melanocytes myosin-Va and kinesin-1 have both been proposed as long-range centrifugal melanosome transporters. Here we investigated the role of kinesin-1 heavy chain (Kif5b) and its suggested targeting factor Rab1a in transport. Using confocal microscopy and sub-cellular fractionation we did not detect Kif5b or Rab1a on melanosomes. Meanwhile functional studies, using siRNA knockdown and dominant negative mutants, did not support a role for Kif5b or Rab1a in melanosome transport. To probe the potential of Kif5b to function in transport we generated fusion proteins that target active Kif5b to melanosomes and tested their ability to rescue perinuclear clustering in myosin-Va deficient cells. Expression of these chimeras, but not full length Kif5b, dispersed melanosomes with similar efficiency to myosin-Va. Our data indicate that kinesin/MT can compensate for defects in myosin-Va/actin-based transport in mammals but that endogenous Kif5b plays little role in transport in melanocytes due to its inefficient recruitment to melanosomes.